Determination of domain structure and abundance of epitaxial Pb(Zr,Ti)O-3 thin films grown on MgO(001) by rf magnetron sputtering - Lee, KS; Kang, YM; Baik, S (MATERIALS RESEARCH SOCIETY, 1999)
Epitaxial Pb(ZrxTi1-x)O-3 (x = 0.0-0.32) ferroelectric thin films of 500 nm thickness were grown on MgO(001) single crystal substrates by in situ rf magnetron sputtering, and evolution of their domain structures is characterized by employing various x-ray diffraction techniques. X-ray theta-2 theta scan showed the films were grown highly c-axis oriented with a tetragonal perovskite structure. 90 degrees domain configuration was investigated using the x-ray rocking curve analysis for PZT 100 peaks in two different phi angles. The rocking curve analysis showed that the degree of c-axis orientation and the crystalline quality of the films were improved continuously with increasing Zr concentration. The c-domain abundance as a function of Zr concentration was quantified using the x-ray rocking curves of PZT 001 and 100, taking account of structural factors and Lorentz-polarization factors. High temperature x-ray technique was also employed to quantify the domain structure as a function of temperature during cooling after reheating the samples to 650 degrees C. During the cooling process, c-domain abundance was found to increase continuously while the crystalline quality of the films was deteriorated below the Curie temperature. The results led us to conclude that the transformation strain of the film at and below the Curie temperature plays a significant role in the final domain structure and abundance of epitaxial PZT thin films.
Keywords: MISFIT RELAXATION MECHANISMS; PULSED-LASER DEPOSITION; PHASE-TRANSFORMATION; STRAIN RELAXATION; PBTIO3; CONFIGURATIONS; MGO; SRTIO3